Effect of shunt reactor rating on the switching transients overvoltage in high voltage system - Al-Tak, Mazyed A.; Ain, Mohd Fadzil; Al-Yozbaky, Omar Sh.; Mohd Jamil, Mohamad Kamarol (Bulletin of Electrical Engineering and Informatics, 2024)
This paper includes a computer simulation of switching transient overvoltages during the disconnecting of shunt reactors (SR). Based on the results of the transient simulations, two reactors (150 MVAr and 50 MVAr) were examined. Reactor current interruption causes significant overvoltages, especially across the reactor and the circuit breaker (CB). The severity of these overvoltages may surpass the voltage level, which might endanger the reactor’s insulation and accelerate the CBs ageing process. For this reason, a significantly modified circuit model is proposed. The results of the field testing showed that the proposed modified circuit technique was successful. The transient overvoltages were computed using ATP-draw simulations of the equivalent circuit during switching. Successful synchronous switching could decrease the electromagnetic and mechanical stress generated during frequent switching operations. The model was examined the switching transient overvoltage for different values of current chopping (0-20) A. The proposed model proved that the reduction of the overvoltage was 86% in case of (50 MVAr) shunt reactor rating and 87% in case of (150 MVAr) shunt reactor rating.